2019
DOI: 10.1016/j.ajog.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the diagnostic accuracy of 3 ultrasound modalities for diagnosing obstetric anal sphincter injuries

Abstract: Comparing the diagnostic accuracy of three ultrasound modalities for diagnosing obstetric anal sphincter injuries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 28 publications
0
44
1
5
Order By: Relevance
“…All study participants gave written informed consent. The current study is a sub-analysis of a study assessing test accuracy of IUS and TPUS compared with EAUS for diagnosis of anal sphincter defects, and a power calculation of this parent study showed that 250 women were needed [17].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All study participants gave written informed consent. The current study is a sub-analysis of a study assessing test accuracy of IUS and TPUS compared with EAUS for diagnosis of anal sphincter defects, and a power calculation of this parent study showed that 250 women were needed [17].…”
Section: Methodsmentioning
confidence: 99%
“…The IUS and TPUS volumes were analysed using tomographic ultrasound imaging (TUI; Fig. 2) [17]. The IAS and EAS were analysed using the same TUI, where the interval between the slices was adjusted according to the individual length of the EAS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoanal ultralyd er ansett som den mest pålitelige metoden for å påvise skade på analsfinkterne, men transperineal ultralyd har også vist seg å vaere godt egnet til å utelukke skade (29). Imidlertid bør funn ved transperineal ultralyd alltid bekreftes med endoanal ultralyd, da førstnevnte har lav positiv prediktiv verdi sammenliknet med sistnevnte (30)(31)(32). Fordelen med transperineal ultralyd er at utstyret er lettere tilgjengelig enn det som brukes ved endoanal ultralyd.…”
Section: Diskusjonunclassified